2016
DOI: 10.1002/fut.21826
|View full text |Cite
|
Sign up to set email alerts
|

Option Market Characteristics and Price Monotonicity Violations

Abstract: This study reexamines whether option price monotonicity properties hold in a liquid market with little market friction and considers the validity of the monotonicity properties in light of option market characteristics. We confirm that option prices do not monotonically correlate with underlying spot prices and that call and put prices often increase or decrease together, indicating that the monotonicity properties are not consistent with the observed option price dynamics. The violations of monotonicity prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Another series of studies examines the Korean options market, which also provides high‐quality microstructure data. Ahn, Kang, and Ryu () and Yang, Choi, and Ryu () conclude that foreign institutional investors have an information edge and that their orders and trades perform significantly better than those of domestic investors. Sim, Ryu, and Yang () claim that domestic individual derivatives traders are noisy and behaviorally biased and demonstrate the inferiority of such investors in terms of informed trading and sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Another series of studies examines the Korean options market, which also provides high‐quality microstructure data. Ahn, Kang, and Ryu () and Yang, Choi, and Ryu () conclude that foreign institutional investors have an information edge and that their orders and trades perform significantly better than those of domestic investors. Sim, Ryu, and Yang () claim that domestic individual derivatives traders are noisy and behaviorally biased and demonstrate the inferiority of such investors in terms of informed trading and sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that global financial markets are integrating (Choi, Ryu, and Yang, 2018 [60]) and that Asian financial markets are similar to the Korean market in terms of investor participation rates, market maturities, and asset price movements, our results may suggest economic and trading implications for market practitioners, investors, and regulators in emerging markets. Further, behavioral bias issues are also monitored by governments and regulators, who design legal systems and carry out market reforms (Ryu and Yang 2018 [61]; Yang, Choi, and Ryu, 2017 [62]; Yang, Ryu, and Ryu, 2018 [57]). Our study provides policy implications for such parties.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistently reported that the information advantages of foreign and domestic investors and their responses to public and private information are quite different in the Korean financial market (Kim, Ryu, & Seo, ; Lee & Chung, ; Ryu, ; Yang, Choi, & Ryu, ). The sample used in this analysis contains more bad news than good news; because foreign investors appear to be more sensitive to bad news, the put‐implied volatility may react more strongly to macroeconomic news announcements.…”
Section: Empirical Findingsmentioning
confidence: 99%